Effect Of Yoga Intervention on Blood Pressure, Heart Rate, and Body Mass Index in Indo-Tibetan Border Police Personnel for High-Altitude Missions in India - Arya, Jaideep; kumar, Saket; Sharma, Sunil; Duhan, Ishwar; Chander, Harish; Priyanka; Jaspreet (International Research Journal of Ayurveda & Yoga, 2024)
Background: The Indo-Tibetan Border Police (ITBP) personnel face unique health challenges due to high-altitude deployments above 3,000 meters. Prolonged exposure to such extreme conditions often leads to hypertension, altered heart rates, and fluctuations in body mass index (BMI). These health issues can adversely affect operational readiness. Yoga, a time-tested practice known to promote physical and mental well-being, has potential therapeutic effects for managing these challenges. This study investigates the impact of a structured yogic regimen on blood pressure, heart rate, and BMI among ITBP personnel.Materials & Methods: This longitudinal intervention study included 100 ITBP personnel, aged 25–45 years, with no history of cardiovascular or metabolic diseases. Participants were selected purposively, ensuring they were stationed at altitudes above 3,000 meters. Pre- and post-intervention measurements of systolic and diastolic blood pressure, heart rate, and BMI were recorded. Statistical analyses were conducted to assess the significance of changes in these parameters.Results:Statistical analysis revealed significant improvements in all measured parameters. Systolic and diastolic blood pressure reduced from mean pre-test values of 121.17 mmHg and 82.67 mmHg to post- test values of 117.53 mmHg and 77.12 mmHg, respectively. Heart rate showed a mean reduction from78.47 to 73.12 beats per minute. BMI decreased from a mean of 22.41 to 21.93 kg/m², demonstrating weight stabilization and improved physical well-being.Conclusion: The study demonstrates that structured Yogic practices significantly enhance cardiovascular health and physical well-being among ITBP personnel in high-altitude regions. The observed reductions in blood pressure, heart rate, and BMI underscore Yoga’s potential as an effective preventive health measure for individuals in high-stress environments. Integrating Yoga into regular health management strategies can enhance operational readiness and overall well-being. Further studies are recommended to explore the long-term benefits and broader occupational applications of Yoga.